Prolaps Organ Panggul - Jacobus Wibisono; Gezta Hermawan (Medicinus, 2019)
Pelvic organ prolapse is a condition of descent or herniation of woman’s pelvic organs through the birth canal or onto birth canal space. As someone gets older, the incidence of pelvic organ prolapse increases, due to weakening of ligaments and muscles as suspensor for the pelvic organs. Prolapse may or may not show symptoms. Symptoms that occur are associated due to pressure of the pelvic area, difficulty urinating and defecation. The staging of pelvic organ prolapse utilized the Baden-Walker System and Pelvic Organ Prolapse Quantification (POP-Q). Management for pelvic organ prolapse can be done conservatively and operatively, and the decision of which approach should be taken based on the patient’s condition and choice.